2021
DOI: 10.21873/invivo.12664
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Struma Ovarii Τreated With Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC)

Abstract: Background/Aim: Malignant struma ovarii is an extremely rare tumor entity among ovarian tumors. In the presence of ascites and peritoneal metastases, the preoperative appearance may resemble the most common epithelial ovarian carcinoma (EOC) and accordingly, the surgical therapy may be identical if a preoperative histology diagnosis is not possible. The objective of this case report is to present a patient with histopathologically confirmed malignant struma ovarii who underwent cytoreductive surgery and hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Some authors recommend routine thyroidectomy followed by I131 treatment, regardless of the presence of metastasis at diagnosis, to avoid local recurrence and distant metastasis. Asc et al [13] reported a case of MSO treated with cell depletion and thermal intraperitoneal chemotherapy. Favorable survival rates (95.3%, 88.7%, and 88.7% at 5, 10, and 20 years of OS, respectively) were found regardless of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommend routine thyroidectomy followed by I131 treatment, regardless of the presence of metastasis at diagnosis, to avoid local recurrence and distant metastasis. Asc et al [13] reported a case of MSO treated with cell depletion and thermal intraperitoneal chemotherapy. Favorable survival rates (95.3%, 88.7%, and 88.7% at 5, 10, and 20 years of OS, respectively) were found regardless of treatment.…”
Section: Discussionmentioning
confidence: 99%